Seleção de sítio de nidificação de Cercomacra melanaria (Tamnophilidae) no Pantanal - Ferreira, Tiago Valadares (2021)
Aspects such as the mating period and nesting site are some factors that are part of the birds' reproduction strategies. Variations in criteria associated with nesting sites depend on choices that are not only related to the quality of the habitat, but also consider the costs and benefits of using a given space. This suggests that there are specific preferences in the conditions of the sites chosen for building the nests. Forest suppression activities, especially anthropogenic ones, directly interfere in the ecology of certain species, such as understory birds, which are more vulnerable to environmental changes. The species Cercomacra melanaria (mato grosso antbird) is a passerine bird that belongs to the Thamnophilidae family and inhabits the dense understory of semideciduous and gallery forests in the Pantanal region. It is most often seen near water walking in pairs, it feeds on invertebrates such as ants, beetles, spiders and caterpillars. The study was carried out in the Pantanal Mato-grossense, in the years 2019 and 2020 between the months of September to December of the respective years, during the reproductive period of the species. This work aimed to test the hypothesis that the selection of nesting sites for C. melanária is related to specific characteristics of the environment such as food availability, proximity to water bodies and canopy cover. An analysis of the probability of success of finding active nests in a given location was used, using the generalized linear model (GLM) based on binomial regression. A total of 198 sites were sampled, where 45 nesting sites were identified and 51 active nests were found. The results of this model show that the selection of a nesting site is related to the availability of food in the environment. Vegetation suppression is the biggest threat to the loss of habitat used by animals, especially those with high forest dependence such as C.melanária. These data are essential to understand the ecological reproductive dynamics of the species and to design more precisely conservation strategies.